Students’ Experiences of Balancing Organizational and Academic Life - Afiifah Nur Alyaa Ibrahim; Khusnul Khatimah; Dzul Rachman (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to explore the experiences of students in balancing their academic responsibilities with their active involvement in a campus organization, specifically MAPALA UMKT (Mahasiswa Pecinta Alam Universitas Muhammadiyah Kalimantan Timur). As student organizations offer valuable opportunities for personal growth, leadership development, and social engagement, they may also present challenges in managing time and maintaining academic motivation. This research uses a qualitative approach with a case study method to understand how students experience, navigate, and reflect on these dual roles. Data were collected through semi-structured interviews with selected MAPALA UMKT members from different cohorts, academic levels, and organizational roles. The results revealed that while organizational involvement can become a source of time pressure and academic stress, it also fosters essential skills such as time management, self-discipline, and problem-solving, which in turn contribute positively to academic motivation. Students' ability to maintain balance often depends on their level of self-regulation, social support, and commitment to both domains. This study highlights the complex yet meaningful relationship between organizational engagement and academic life, offering insights for universities, student organizations, and students themselves in building better support systems and fostering holistic student development.